(untitled) (Hoboken, New Jersey, 2016)
This book provides: - A geographical overview of key local specificities and trends in major M&​A markets: Australia, Benelux, Brazil, China, France, Germany, Africa, Indonesia, Israel, Nordic, Russia, U.K., and U.S. - An understanding of the most important specificities to deal with in some regions. - Guidance for global M&​A practitioners: PE firms, Investment Bankers, Corporations, Consultants, Professional Service Firms (e.g. Legal, Accounting). - Coverage for various industries including: Aerospace and Defense, Financial service (Banking, Insurance, Financial institutions), Construction and Civil Engineering, Telecommunications, High Tech, Health care (Pharma, Hospitals, Manufacturers, Service Providers) and Public institutions (Central Administrations, Public Agencies, Schools, Armies). - Understanding for cultural impacts to cross border transactions and integration. - Practical advice and tools from seasoned professionals who have collectively managed several hundred M&​A transactions (mergers, acquisitions, carve-outs, etc.). - Guidance for managing carve outs--one of the most complex and difficult aspects of cross border deals. - Greater visibility around critical path items that enable success in cross-border M&​A. - Practical know-how on leading integration efforts globally. - Examples of best practices and lessons learned of actual PMI processes that were led by top notch experts. - Examples of tools, templates, and processes for cross border PMI. - Country specific examples for readers with specific situational needs
Keywords: Hợp nhất và sáp nhập các tập đoàn,Consolidation and merger of corporations